Adaptive Integrated Guidance and Fault Tolerant Control Using Backstepping and Sliding Mode - Mohsen Fathi Jegarkandi; Asghar Ashrafifar; Reza Mohsenipour (International Journal of Aerospace Engineering)
A new method of integrated guidance and control for homing missiles with actuator fault against manoeuvring targets is proposed. Model of the integrated guidance and control system in the pitch plane with actuator fault and some uncertainty is developed. A control law using combination of adaptive backstepping and sliding mode approaches is designed to achieve interception in the presence of bounded uncertainties and actuator fault. Simulation results show that new approach has better performance than adaptive backstepping and has good performance in the presence of actuator fault.